Intragenic rearrangements in X‐linked intellectual deficiency: Results of a‐CGH in a series of 54 patients and identification of TRPC5 and KLHL15 as potential XLID genes. Issue 8 (9th May 2014) - Mignon‐Ravix, Cécile; Cacciagli, Pierre; Choucair, Nancy; Popovici, Cornel; Missirian, Chantal; Milh, Mathieu; Mégarbané, André; Busa, Tiffany; Julia, Sophie; Girard, Nadine; Badens, Catherine; Sigaudy, Sabine; et al.
<x xml:space="preserve">Abstract</x> High‐resolution array comparative genomic hybridization (a‐CGH) enables the detection of intragenic rearrangements, such as single exon deletion or duplication. This approach can lead to the identification of new disease genes. We report on the analysis of 54 male patients presenting with intellectual deficiency (ID) and a family history suggesting X‐linked (XL) inheritance or maternal skewed X‐chromosome inactivation (XCI), using a home‐made X‐chromosome‐specific microarray covering the whole human X‐chromosome at high resolution. The majority of patients had whole genome array‐CGH prior to the selection and we did not include large rearrangements such as MECP2 and FMR1 duplications. We identified four rearrangements considered as causative or potentially pathogenic, corresponding to a detection rate of 8%. Two CNVs affected known XLID genes and were therefore considered as causative (IL1RAPL1 and OPHN1 intragenic deletions). Two new CNVs were considered as potentially pathogenic as they affected interesting candidates for ID. The first CNV is a deletion of the first exon of the TRPC5 gene, encoding a cation channel implicated in dendrite growth and patterning, in a child presenting with ID and an autism spectrum disorder (ASD). The second CNV is a partial deletion of KLHL15, in a patient with severe ID, epilepsy, and anomalies of cortical development. In both cases, in spite of strong arguments for clinical relevance, we were not able at this stage to confirm pathogenicity of the mutations, and the causality of the variants identified in XLID remains to be confirmed. © 2014 Wiley Periodicals, Inc.